2022
DOI: 10.3389/fmicb.2022.955112
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-enriched Bifidobacterium longum DD98 effectively ameliorates dextran sulfate sodium-induced ulcerative colitis in mice

Abstract: The pathogenesis of ulcerative colitis (UC) is complicated with impaired intestinal epithelial barrier and imbalanced gut microbiota. Both selenium and probiotics have shown effects in regulating intestinal flora and ameliorating UC. The objective of this study is to investigate the alleviating effects of Selenium-enriched Bifidobacterium longum DD98 (Se-B. longum DD98) on dextran sulfate sodium (DSS)-induced colitis in mice and explore the underlying mechanism. After treatment of B. longum DD98, Se-B. longum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…26 And B. longum DD98 could increase the expression of tight junction protein in DSS-induced colitis, including ZO-1 and Occludin. 32 Moreover, the ameliorating effects of other Bifidobacterium strains on colitis showed to be related to their restoration of tight junction integrity, including B. breve , B. pseudocatenulatum , and B. bifidum . 21,27,33,34…”
Section: Discussionmentioning
confidence: 99%
“…26 And B. longum DD98 could increase the expression of tight junction protein in DSS-induced colitis, including ZO-1 and Occludin. 32 Moreover, the ameliorating effects of other Bifidobacterium strains on colitis showed to be related to their restoration of tight junction integrity, including B. breve , B. pseudocatenulatum , and B. bifidum . 21,27,33,34…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the gut microbiota modulatory effect between Bifidobacterium adolescentis B8598 and probiotic strains used in previous fecal microbiome-based studies in experimental colitis mouse model are summarized in Supplementary Table 5 19,22,25,29,31,32,[41][42][43][44][45] . Our results were similar to the observation of several previous reports that the phylum-level fecal microbiota did not show obvious changes subjected to probiotic supplementation 22,29,31,32,41,44 . Two studies identified significant changes in the species-level fecal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the abuse of broad-spectrum antibiotics claims for the gastrointestinal barrier impairment via inhibiting the symbiotic bacteria, allows the infiltration of pathogenic bacteria and its detrimental metabolites into the circulation cycle. Conversely, increasing the number of probiotics is beneficial for gut microbiota function [ 61 ]. The Western diet (WD) is a crucial reason for systemic inflammation and cognitive decline in mice.…”
Section: Enterotype and Inflammatory Responsesmentioning
confidence: 99%